“El aprendizaje y los recursos tecnológicos en la asignatura de Ciencias Naturales” - Cañar Taipe, Evelyn Johana (2022)
Science and technology in the 21 st century, it is paramount in any social field, but even more so in the focused educational field on knowledge areas, such as the natural sciences, since children and young people need technology to increase knowledge, therefore, education requires foundations to be able to manage, use and expand the mechanisms, which used by teacher today. The researchers team set out the following aims to demonstrate how affect technological resources the natural sciences subject teaching-learning process in the fourth grade "19 de Septiembre" Educational Unit, Salcedo Canton, 2021-2022 school year, immediately, to base the theoretical, technological resources and references learning in the natural sciences subject, therefore, to design an audiovisual technological resources in the natural sciences subject, finally, to design an audiovisual technological aid for the learning development into natural sciences, which was achieved to express themselves. Through this project, it was proposed an orientation to teachers, mainly, in the natural sciences subject, what will allow them to elaborate didactic material, where the student is the attention center, dynamiting their classes, by getting a different school environment, thus the students will feel the learning satisfaction in an interesting way. The methodology this project, it was based on qualitative research, because it allowed to delve into going into the educational context reality, for observing the environment, where it was developed teachers and students, the used method was inductive with documentary or bibliographic, descriptive and in the field, the data were got, through the observation, interview and survey techniques with their interview guide instruments and questionnaire, for collecting information and study object important data. The result this research work focuses on making a video guide for children in the urban sector, in order to present teachers with an innovative teaching-learning alternative. Finally, this project contributes with various technological resource, what support the teaching work, facilitating student learning, so that there is a content better understanding and capture transmitted, through innovative, creative resources and thus, getting significant learning, therefore, it is pointed out that technological tools, this century play a transcendent role in the students inter-learning processes.